TINGKAT KECEMASAN IBU DALAM MENGHADAPI PROSES PERSALINAN NORMAL DI KLINIK ALISA PRATAMA KEL. KENTEN KAB. BANYUASIN TAHUN 2022 - Desi Hariani; Elvina Indah Syafriani; Era Mardia Sari (Jurnal Kesehatan dan Pembangunan, 2024)
The process of delivery is influenced by some factors such as passage, passanger, power and helpers, psychological factors are also very determine the success delivery. Where anxiety or tension, insecurity and anxiety arising from perceived unpleasantness occur but the source is largely unknown and originating from within (intra-psychic) ??may result in prolonged delivery or extension of phase II (Depkes RI Pusdiknakes) . The aim of this study is to know the description of mother anxiety to face normal delivery at Clinic Alisa Pratama Ward Kenten Regency Banyuasin Years 2022. This study used quantitative Descriptive method. The sample size was 30 respondents were taken with porposive sampling technique. The result of the study showed that women who experienced anxiety were 18 (60%), mothers with anxiety were 8 (26,7%), mothers who had severe anxiety 3 (10%), and mothers with severe anxiety (Panic) 1 (3.3%) Based on the results of this study, it is suggested to health officers to be more improve the quality of midwifery services especially in terms of emotional support of patients.